New functional ingredients from Salvia sclareoides for the prevention of Alzheimer´s disease - Abraços, L. (2019)
Salvia sclareoides is a plant of spontaneous Portuguese vegetation that has relevant properties, as part of its cholinergic action and in the prevention of the formation of amyloid plaques. Previous studies suggested1,2 that this species of Salvia can be used as a functional food and also in the development of a food supplement in the context of the prevention and treatment of Alzheimer's disease. Salty cookies were developed with the incorporation of different concentrations (2% and 5%) of S. Sclareoides. The nutritional composition of the cookies was determined, namely: fatty acid profile3, moisture content, ash, total protein, total fat3, dietary fibre and salt3. The available carbohydrates and the energetic value were obtained by calculation. Ethanol extracts from the salty cookies were prepared to evaluate the antioxidant (DPPH) and anticholinesterase (Ellman method) activities. Total phenolic content was evaluated by the Folin-Ciocalteu1 method and the phenolic composition was analysed by high performance liquid chromatography with diode array detection. The ethanol extracts of the cookies with 5% of S. sclareoides showed the best acetylcholinesterase inhibition (44.4%), the highest concentration of phenolic compounds (22.78 mg GAE/g dry extract), and antioxidant activity (10.3%). The flavonoids rutin and (7-O-glucosyl)luteolin are clearly the major constituents present in the extracts, along with epicatechin, ellagic acid, and (7-O-glucosyl) naringenin. The incorporation of this plant in the cookies formulation resulted in a pleasant and nutritionally interesting functional product with potential application in the prevention of neurodegenerative diseases.